Hadis Azimat Perspektif Semiotik Roland Barthes - Huda, Syafi'ul (POROS ONIM: Jurnal Sosial Keagamaan, 2021)
As a cultured country, the ancestors of the Indonesian people bequeathed a lot of relics that are represented in norms and objects.  Regarding norms, the harmony of the Indonesian nation which is multicultural, multiethnic, and multireligious has become irrefutable evidence.  It is different with relics in the form of material.  Some of them still leave endless debates when they are met with religion.  Amulet, for example, some people consider it as an element of polytheism that must be avoided.  Meanwhile, the majority of the existing community has no problem with its use as long as it is in accordance with the provisions outlined by the pious scholar.  The views of these two groups are based on the same source, namely the hadith of the Prophet Muhammad (Peace be upon Him). Nevertheless, the approaches used in the understanding are completely different, so that they have their own prespective views. The derivation of the passages that appear in the understanding of the two groups into the charts provided by Roland Barthes in his mythical semiology is very helpful for ordinary people to recognize these two views.